Temperature-influenced deformation analysis of a full-scale steel-concrete-steel cable support tower model during construction - Zhi-Li Qi; Wei-Le Chen; Jian Li; Jian-Sheng Fan; Rong Xian; Fei Tian; Yu-Fei Liu (Engineering Structures, 2026)

Highly antifouling field-effect transistor biosensors: From interface design to practical applications - Jiajun Tong; Rong Mu; Luming Zhi; Ruilian Yu; Kemin Wang; Zijun Zhao; Yiwei Liu; Taiping Qing; Xiaofeng Liu (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

A CBAM-integrated deep convolutional neural network for weather radar echo correction to overcome terrain occlusion challenge - Hao Wang; Zhihao Liu; Fugui Zhang; Zhi Li; Qiangyu Zeng; Tiantian Yu; Rong Yang (Advances in Space Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Exhumation history of the eastern Tethyan Himalaya: Evidence from Apatite (U Th)/He Thermochronology - Xu Han; Jin-Gen Dai; Bo-Rong Liu; Zhi-Cheng Yu (Tectonophysics, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Room temperature natural light promoted DMSO/O2-catalyzed N-acylation reaction of imidazoles/triazoles with cyclopropenones - Guo-Dong Shen; Zhi-Rong Zhao; Kun Bi; Yi Man; Jun-Tong Liu; Xian-Qiang Huang; Xin Lv (Molecular Diversity, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sophormodines A−C, three alkaloids with antiviral activities against the HBV from the seeds of the Tibetan medicine plant Sophora moorcroftiana - Ting-Ting Liu; Meng-Fan Xie; Qing-Qing Yang; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

High-efficiency immobilization of soil available cadmium by chicken manure and its derivatives: Roles of chemical and microbial property - Zhi-Wen Hu; Feng Jiang; Fei Huang; Heng Wang; Qian-Jun Liu; Xiao Zhou; Ming-Zhi Huang; Peng Wang; Rong-Bo Xiao (Journal of Environmental Chemical Engineering, 2025)

Improved rainfall infiltration model for probabilistic slope stability assessment considering transition layers and spatial variability - Shui-Hua Jiang; Zhi-Rong Yuan; Ze Zhou Wang; Xian Liu (Engineering Geology, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Monitoring-based analysis of the responses of upper structure and tunnel lining during shield tunneling with pile cutting - Zhi-Xiong Liu; Xiao-Wei Ye; Ke Song; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Precipitation patterns strongly affect vertical migration and methylation of mercury in legacy contaminated sites - Xujun Liang; Zhi-Cheng Hu; Yu-Rong Liu; Cunbin Gao; Yi Zhang; Yun-Yun Hao; Lijie Zhang; Jiating Zhao; Lizhong Zhu (Water Research, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Index construction and real-time hazard assessment of rice sterile-type chilling injury process in Northeast China - Bilige Sudu; Kaiwei Li; Suri Guga; Teri Gele; Feng Zhi; Ying Guo; Sicheng Wei; Guangzhi Rong; Yongbin Bao; Xingpeng Liu; Jiquan Zhang (Agricultural and Forest Meteorology, 2024)

Building a stable and robust anti-interference DNA dissipation system by eliminating the accumulation of systemic specified errors - Luojia Wang; Wang Luo; Zhi Weng; Zhongzhong Wang; You Wu; Rong Zhao; Xiaole Han; Xin Liu; Jianhong Zhang; Yujun Yang; Guoming Xie (Analytica Chimica Acta, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Mesoscopic measurement of damage and shear bands of granite residual soil using Micro-CT and digital volume correlation - Cheng-sheng Li; Bing-xin Zhang; Zhi-jun Liu; Ling-wei Kong; Rong-jun Shu (Journal of Mountain Science, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Amendments of nitrogen and sulfur mitigate carbon-promoting effect on microbial mercury methylation in paddy soils - Yunyun Li; Shu-Shen Dai; Jiating Zhao; Zhi-Cheng Hu; Qin Liu; Jiao Feng; Qiaoyun Huang; Yuxi Gao; Yu-Rong Liu (Journal of Hazardous Materials, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Chemical constituents from the root bark of Morus alba and their chemotaxonomic significance - Xiao-Cong Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

An in silico and in vitro integrated analysis method to reveal the curative mechanisms and pharmacodynamic substances of Bufei granule on chronic obstructive pulmonary disease - Yuan-yuan Ma; Rong Li; Zhi-xian Shang; Wei Liu; Xin-yi Jiao; Liu-yi Liang; Rui Liu; Zheng Li (Molecular Diversity, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Plastid diversity and chromoplast biogenesis in differently coloured carrots: role of the DcOR3Leu gene - Yu-Min Zhang; Rong-Hua Wu; Lu Wang; Ya-Hui Wang; Hui Liu; Ai-Sheng Xiong; Zhi-Sheng Xu (Planta, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Effect of oxygen concentrations and branched‐chain amino acids on the growth and development of sub‐seafloor fungus, Schizophyllum commune 20R‐7‐F01 - Muhammad Zain Ul Arifeen; Zhi‐Jun Ma; Si Wu; Jun‐Zhong Liu; Ya‐Rong Xue; Chang‐Hong Liu (Environmental Microbiology, 2021)
Summary Fungi have been reported to be the dominant eukaryotic group in anoxic sub‐seafloor sediments, but how fungi subsist in the anoxic sub‐marine sedimental environment is rarely understood. Our previous study demonstrated that the fungus, Schizophyllum commune 20R‐7‐F01 isolated from a ~2 km sediment below the seafloor, can grow and produce primordia in the complete absence of oxygen with enhanced production of branched‐chain amino acids (BCAAs), but the primordia cannot be developed into fruit bodies without oxygen. Here, we present the individual and synergistic effects of oxygen and BCAAs on the fruit‐body development of this strain. It was found that the fungus required a minimum oxygen concentration of 0.5% pO 2 to generate primordia and 1% pO 2 to convert primordia into mature fruit body. However, if BCAAs (20 mM) were added to the medium, the primordium could be developed into fruit body at a lower oxygen concentration up to 0.5% pO 2 where genes fst4 and c2h2 playing an important role in compensating oxygen deficiency. Moreover, under hypoxic conditions, the fungus showed an increase in mitochondrial number and initiation of auto‐phagocytosis. These findings suggest that the fruit‐body formation of S. commune may have multiple mechanisms, including energy and amino acid metabolism in response to oxygen concentrations.

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Sea surface salinity-derived indexes for distinguishing two types of El Niño events in the tropical Pacific - Hai Zhi; Pengfei Lin; Zhujun Fang; Hailong Liu; Rong-Hua Zhang; Wenrong Bai (Science China Earth Sciences, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Biocontrol mechanism of Myxococcus fulvus B25-I-3 against Phytophthora infestans and its control efficiency on potato late blight - Zhi Hua Wu; Qiang Ma; Zhi Ning Sun; Hai Chen Cui; Hui Rong Liu (Folia Microbiologica, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Translocator protein 18 kDa: a potential therapeutic biomarker for post traumatic stress disorder - Zhi-Kun Qiu; Xu Liu; Yong Chen; Rong-Jia Wu; Shi-Feng Guan; Yun-yun Pan; Qian-Bo Wang; Dan Tang; Tao Zhu; Ji-Sheng Chen (Metabolic Brain Disease, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Salinity effects on the 2014 warm “Blob” in the Northeast Pacific - Hai Zhi; Pengfei Lin; Rong-Hua Zhang; Fei Chai; Hailong Liu (Acta Oceanologica Sinica, 2019)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

Magnetic characteristics of Juniperus formosana needles along an urban street in Lanzhou, Northwest China: the variation of different season and orientation - Hong Chen; Bo Wang; Dun-sheng Xia; Yi-jiao Fan; Hui Liu; Zhi-rong Tang; Shan Ma (Environmental Science and Pollution Research, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Schinzel–Giedion syndrome: a novel case, review and revised diagnostic criteria - Wei-Liang Liu; Zhi-Xu He; Fang Li; Rong Ai; Hong-Wei Ma (Journal of Genetics, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Zn(II)-dipicolylamine-based metallo-lipids as novel non-viral gene vectors - Rong-Chuan Su; Qiang Liu; Wen-Jing Yi; Zhi-Gang Zhao (JBIC Journal of Biological Inorganic Chemistry, 2017)

Effect of Co-overexpression of Nisin Key Genes on Nisin Production Improvement in Lactococcus lactis LS01 - Zhi-Jian Ni; Xiao-yuan Zhang; Fei Liu; Miao Wang; Rong-hua Hao; Pei-xue Ling; Xi-Qiang Zhu (Probiotics and Antimicrobial Proteins, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Dual-Labeled Time-Resolved Immunofluorometric Assay for the Simultaneous Quantitative Detection of Hepatitis B Virus Antigens in Human Serum - Rong-Liang Liang; Yun-Sen Yang; Jian-Wei Zhou; Tian-Cai Liu; Xu-Ping Xu; Qian-Ni Liang; Zhen-Hua Chen; Zhi-Ning Dong; Ying-Song Wu (Journal of Fluorescence, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Hydrogen sulfide alleviates zinc toxicity by reducing zinc uptake and regulating genes expression of antioxidative enzymes and metallothioneins in roots of the cadmium/zinc hyperaccumulator Solanum nigrum L. - Xiang Liu; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Zhi-Jun Shen; Mei-Rong Luo; Gui-Feng Gao; Martin Simon; Kabir Ghoto; Hai-Lei Zheng (Plant and Soil, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Zinc binds to and directly inhibits protein phosphatase 2A in vitro - Yan Xiong; Dan-Ju Luo; Xiu-Lian Wang; Mei Qiu; Yang Yang; Xiong Yan; Jian-Zhi Wang; Qi-Fa Ye; Rong Liu (Neuroscience Bulletin, 2015)

Removal of antibiotics and antibiotic resistance genes in rural wastewater by an integrated constructed wetland - Jun Chen; You-Sheng Liu; Hao-Chang Su; Guang-Guo Ying; Feng Liu; Shuang-Shuang Liu; Liang-Ying He; Zhi-Feng Chen; Yong-Qiang Yang; Fan-Rong Chen (Environmental Science and Pollution Research, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

Inverse associations of outdoor activity and vitamin D intake with the risk of Parkinson’s disease - Dan Zhu; Gui-you Liu; Zheng Lv; Shi-rong Wen; Sheng Bi; Wei-zhi Wang (Journal of Zhejiang University-SCIENCE B, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Light-regulated phosphorylation of maize phosphoenolpyruvate carboxykinase plays a vital role in its activity - Qing Chao; Xiao-Yu Liu; Ying-Chang Mei; Zhi-Fang Gao; Yi-Bo Chen; Chun-Rong Qian; Yu-Bo Hao; Bai-Chen Wang (Plant Molecular Biology, 2014)

Auditory sexual difference in the large odorous frog Odorrana graminea - Wei-Rong Liu; Jun-Xian Shen; Yu-Jiao Zhang; Zhi-Min Xu; Zhi Qi; Mao-Qiang Xue (Journal of Comparative Physiology A, 2014)

Age and composition of the Rebang Co and Julu ophiolites, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Wei-Liang Liu; Bin Xia; Yun Zhong; Jian-Xin Cai; Jian-Feng Li; Hong-Fei Liu; Zhou-Rong Cai; Zhi-Lei Sun (International Geology Review, 2014)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Impact of nodular size on the predictive values of gray-scale, color-Doppler ultrasound, and sonoelastography for assessment of thyroid nodules - Yu-rong Hong; Yu-lian Wu; Zhi-yan Luo; Ning-bo Wu; Xue-ming Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Solid Lipid Nanoparticles Loaded with Anti-microRNA Oligonucleotides (AMOs) for Suppression of MicroRNA-21 Functions in Human Lung Cancer Cells - San-Jun Shi; Zhi-Rong Zhong; Jie Liu; Zhi-Rong Zhang; Xun Sun; Tao Gong (Pharmaceutical Research, 2012)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Complete genome sequence of a tomato spotted wilt virus isolate from China and comparison to other TSWV isolates of different geographic origin - Zhong-Ze Hu; Zhi-Ke Feng; Zhi-Jun Zhang; Yao-Bin Liu; Xiao-Rong Tao (Archives of Virology, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Inhibition of oestrogen biosynthesis induces mild anxiety in C57BL/6J ovariectomized female mice - Fan-Tao Meng; Rong-Jun Ni; Zhi Zhang; Jun Zhao; Ya-Jing Liu; Jiang-Ning Zhou (Neuroscience Bulletin, 2011)

Molecular characterization of a wheat -Thinopyrum ponticum partial amphiploid and its derived substitution line for resistance to stripe rust - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Zu-Jun Yang (Journal of Applied Genetics, 2011)

Azoospermia related to a unique karyotype: 45,XY,−13,−19,+der(19)t(13;19)(q12;p13) - Chao Fu; Xin Yun; Yuan Dong; Bai-Yan Wu; Rong-Rong Han; Rui-Zhi Liu (Journal of Applied Genetics, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Inhalable Microparticles as Carriers for Pulmonary Delivery of Thymopentin-Loaded Solid Lipid Nanoparticles - Yan-Zhen Li; Xun Sun; Tao Gong; Jie Liu; Jiao Zuo; Zhi-Rong Zhang (Pharmaceutical Research, 2010)

Differential expression of TRPC channels in the left ventricle of spontaneously hypertensive rats - Fang-fang Liu; Zhi-yong Ma; Duo-ling Li; Jin-bo Feng; Kai Zhang; Rong Wang; Wei Zhang; Li Li; Yun Zhang (Molecular Biology Reports, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Alternative splicing in exon 9 of glucocorticoid receptor pre-mRNA is regulated by SRp40 - Xue-Bo Yan; Chen-Hong Tang; Yan Huang; Hui Fang; Zhi-Qiang Yu; Li-Min Wu; Rong-Yu Liu (Molecular Biology Reports, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

New cyclopentenones from strain Trichoderma sp. YLF-3 - Guo-Hong Li; Li-Jun Zheng; Fang-Fang Liu; Li-Zhi Dang; Lei Li; Rong Huang; Ke-Qin Zhang (Natural Product Research, 2009)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Effect of Temperature on Iron Leaching from Bauxite Residue by Sulfuric Acid - Zhi-Rong Liu; Kai Zeng; Wei Zhao; Ying Li (Bulletin of Environmental Contamination and Toxicology, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Overexpression of CyclinD1 and underexpression of p16 correlate with lymph node metastases in laryngeal squamous cell carcinoma in Chinese patients - Zhi-jie Fu; Zhi-yong Ma; Qi-rong Wang; Da-peng Lei; Rong Wang; Chun-xi Liu; Xin-liang Pan (Clinical & Experimental Metastasis, 2008)

Effect of tramadol on immune responses and nociceptive thresholds in a rat model of incisional pain - Yong-min Liu; Sheng-mei Zhu; Kui-rong Wang; Zhi-ying Feng; Qing-lian Chen (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Study on the prediction of visible absorption maxima of azobenzene compounds - Jun-na Liu; Zhi-rong Chen; Shen-feng Yuan (Journal of Zhejiang University-SCIENCE B, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

The promoter of a rice glycine-rich protein gene, Osgrp-2, confers vascular-specific expression in transgenic plants - Zong-Zhi Liu; Jian-Long Wang; Xun Huang; Wei-Hui Xu; Zhao-Ming Liu; Rong-Xiang Fang (Planta, 2003)

Application of geographical parameter database to establishment of unit population database - Chun Dong; Rong Zhao; Ji-ping Liu; Gui-xin Wang; Xi-zhi Wu (Chinese Geographical Science, 2003)

Evaluation of Aegilops tauschii Cosson for preharvest sprouting tolerance - Liu Deng-Cai; Lan Xiu-Jin; Wang Zhi-Rong; Zheng You-Liang; Zhou Yong-Hong; Yang Jun-Liang; Yen Chi (Genetic Resources and Crop Evolution, 1998)

Inheritance in synthetic hexaploid wheat ‘RSP’ of sprouting tolerance derived from Aegilops tauschii Cosson - Lan Xiu-Jin; Liu Deng-Cai; Wang Zhi-Rong (Euphytica, 1997)